Effects of exercise on somatosensory-evoked potentials - Bulut, S; Özmerdivenli, R; Bayer, H (Taylor & Francis Ltd, 2003)
The aim of this study was to investigate the effect of acute and regular exercise on somatosensory-evoked potentials (SEP). The study group was designed as 9 female and 7 mate volleyball players, and the control group as 9 female and 7 male sedentary students. The P1 and P2 latency and amplitude values were measured by tibial nerve stimulation on both lower extremities in the study groups before and after exercise on a treadmill. Intra-group comparison was made to evaluate the acute effects of exercise, and inter-group comparison for the chronic effects of it. Statistically significant difference was determined in pre-exercise right P2 amplitudes and post-exercise left P2 latencies of female volleyball players and sedentary girls. There was significant difference between only the pre-exercise left P2 latency when comparison was made between the sportsmen and sedentary mate subject groups. There were significant differences between the pre-exercise left PI and P2 latency values of sportswomen and right P2 amplitudes of sedentary female subjects. There was no significant difference between left P2 latency values of sportsmen and sedentary male subjects. In conclusion, it was determined that acute and regular exercise shortened the latency of sensory-evoked potentials while decreasing their amplitudes. When evaluating the sensory-evoked potentials in electrophysiology laboratories, the exercise capacity and physical activity levels of the subjects should be considered.
Keywords: exercise; somatosensory-evoked potentials